2016
DOI: 10.1209/0295-5075/116/40007
|View full text |Cite
|
Sign up to set email alerts
|

The Leggett-Garg inequality and Page-Wootters mechanism

Abstract: Violation of the Leggett-Garg inequality (LGI) implies quantum phenomena. In this light we establish that the Moreva et al. [21] experiment demonstrating the Page-Wootter's mechanism [3] falls in the quantum domain. An observer outside a 2-photons world does not detect any change in the 2−photons state,i.e. there is no time parameter for the outside observer. But an observer attached to one of the photons sees the other photon evolving and this means there is an "internal" time. The LGI is violated for the clo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…We show that one obtains the correct quantum correlations and we use this to test the Leggett-Garg inequality [14] (which, in this framework, was suggested in [15]). One of the main criticisms of the PW mechanism was that it seemed unable to provide the correct two-time correlations [7,8,16].…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…We show that one obtains the correct quantum correlations and we use this to test the Leggett-Garg inequality [14] (which, in this framework, was suggested in [15]). One of the main criticisms of the PW mechanism was that it seemed unable to provide the correct two-time correlations [7,8,16].…”
mentioning
confidence: 80%
“…Since we can access arbitrary two-time correlation measurements, we can show that our experiment has a quantum behavior through a violation of the LeggettGarg inequality [14,15]. This inequality is constructed using an observable Q(t) of a two-level physical system, the photon's polarization in our case [18], with |H , |V corresponding to Q = +1, −1 respectively.…”
Section: Leggett-gargmentioning
confidence: 99%
“…A wide range of various quantum system violates the upper bound of LGI and that let the LGI to use it to probe the quantum mechanics (QM) in the macroscopic regime [12][13][14][15][16][17][18][19][20][21][22][23][24]. A detailed review about LGI can be found in [25].…”
Section: Leggett-garg Inequalitymentioning
confidence: 99%